Fetal growth and maternal glomerular filtration rate: a systematic review. (12th December 2015) - Vesterinen, Hanna M.; Johnson, Paula I.; Atchley, Dylan S.; Sutton, Patrice; Lam, Juleen; Zlatnik, Marya G.; Sen, Saunak; Woodruff, Tracey J.
Abstract: Objective : Glomerular filtration rate (GFR) may influence concentrations of biomarkers of exposure and their etiologic significance in observational studies of associations between environmental contaminants and fetal growth. It is unknown whether the size of a developing fetus affects maternal GFR such that a small fetus leads to reduced plasma volume expansion (PVE), reduced GFR and subsequent higher concentrations of biomarkers in maternal serum. Our objective was to answer the question: "Is there an association between fetal growth and maternal GFR in humans?" Methods : We adapted and applied the Navigation Guide systematic review methodology to assess the evidence of an association between fetal growth and GFR, either directly or indirectly via reduction in PVE. Results : We identified 35 relevant studies. We rated 31 human and two non-human observational studies as "low" quality and two experimental non-human studies as "very low" quality. We rated all three evidence streams as "inadequate". The association between fetal growth and GFR was "not classifiable" according to pre-specified definitions. Conclusions : There is currently insufficient evidence to support the plausibility of a reverse causality hypothesis for associations between exposure to environmental chemicals during pregnancy and fetal growth. Further research would be needed to confirm or disprove this hypothesis.